Thermal Bed Design for Temperature-Controlled DNA Amplification Using Optoelectronic Sensors - Guillermo Garcia-Torales; Hector Hugo Torres-Ortega; Ruben Estrada-Marmolejo; Anuar B. Beltran-Gonzalez; Marija Strojnik (Sensors)
Loop-Mediated Isothermal Loop-Mediated Isothermal Amplification (LAMP) is a widely used technique for nucleic acid amplification due to its high specificity, sensitivity, and rapid results. Advances in microfluidic lab-on-chip (LOC) technology have enabled the integration of LAMP into miniaturized devices, known as <semantics>μ</semantics>-LAMP, which require precise thermal control for optimal DNA amplification. This paper introduces a novel thermal bed design using PCB copper traces and <semantics>FR−4</semantics> dielectric materials, providing a reliable, modular, and repairable heating platform. The system achieves accurate and stable temperature control, which is critical for <semantics>μ</semantics>-LAMP applications, with temperature deviations within ±1.0 °C. The thermal bed’s performance is validated through finite element method (FEM) simulations, showing uniform temperature distribution and a rapid thermal response of 2.5 s to reach the target temperature. These results highlight the system’s potential for applications such as disease diagnostics, biological safety, and forensic analysis, where precision and reliability are paramount.